Complete mitochondrial genome of the highly fecund Bombyx mori linnaeus, 1758 (Lepidoptera: Bombycidae) strain Jam 146. Issue 8 (3rd August 2021) - Kim, Seong-Wan; Park, Jeong Sun; Kim, Min Jee; Kim, Kee-Young; Kim, Seong-Ryul; Kim, Iksoo
Abstract: To meet the increasing demands of the society in the current era, new strains of the domesticated silkworm Bombyx mori Linnaeus, 1758 (Lepidoptera: Bombycidae) are being continuously bred. Consequently, cataloging the genetic information of pure lines is essential. The strain Jam 146, whose larvae have atypical pale, crescent-shaped body markings, is an important breeding resource due to its excellent fecundity. In this study, we sequenced the mitochondrial genome (mitogenome) of this strain using next-generation sequencing. The complete genome of this strain has a gene arrangement typical of Lepidoptera. The length of the Jam 146 mitogenome (15, 661 bp) is well within the range reported in other B. mori strains, i.e. between 15, 629 (Baiyun strain, China) and 15, 676 bp (Hukpyobeom strain, South Korea). However, the total length of protein-coding genes, 3, 733 codons in Jam 146 and two other silkworm strains previously reported from South Korea, is 13 codons longer than that in other B. mori strains. Phylogenetic analysis of 22 silkworm strains from nine countries showed that the Jam 146 strain forms a strong cluster with three other strains from China, Japan, and South Korea, suggesting that after their split from a common ancestor, the evolutionary divergence among the silkworm strains in these countries has been limited.